Predictors of patient adherence to COPD self-management exacerbation action plans. Issue 1 (January 2021) - Schrijver, Jade; Effing, Tanja W.; Brusse-Keizer, Marjolein; van der Palen, Job; van der Valk, Paul; Lenferink, Anke
Highlights: 38 % of the patients showed (sub)optimal adherence to COPD exacerbation action plans. Multiple adherence categories provide detailed insight in patient's action plan use. Patient characteristics should be evaluated to shed light on non-adherence. Dyspnoea and cardiac disease are potential predictors of lower patient adherence. Abstract: Objective: Identifying patient characteristics predicting categories of patient adherence to Chronic Obstructive Pulmonary Disease (COPD) exacerbation action plans. Methods: Data were obtained from self-treatment intervention groups of two COPD self-management trials. Patients with ≥1 exacerbation and/or ≥1 self-initiated prednisolone course during one-year follow-up were included. Optimal treatment was defined as 'self-initiating prednisolone treatment ≤2 days from the onset of a COPD exacerbation'. Predictors of adherence categories were identified by multinomial logistic regression analysis using patient characteristics. Results: 145 COPD patients were included and allocated to four adherence categories: 'optimal treatment' (26.2 %), 'sub optimal treatment' (11.7 %), 'significant delay or no treatment' (31.7 %), or 'treatment outside the actual exacerbation period' (30.3 %). One unit increase in baseline dyspnoea score (mMRC scale 0–4) increased the risk of 'significant delay or no treatment' (OR 1.64 (95 % CI 1.07−2.50)). Cardiac comorbidity showed a borderline significant increased risk of 'treatment outside the actual exacerbation period' (OR 2.40 (95 % CI 0.98−5.85)). Conclusion: More severe dyspnoea and cardiac comorbidity may lower adherence to COPD exacerbation action plans. Practice implications: Tailored self-management support with more focus on dyspnoea and cardiac disease symptoms may help patients to better act upon increased exacerbation symptoms and improve adherence to COPD exacerbation action plans.